TRIB3 Promotes the Malignant Progression of Bladder Cancer: An Integrated Analysis of Bioinformatics and in vitro Experiments - Yang, Jieping; Lin, Jiaxing; An, Jun; Zhao, Yongkang; Jing, Siyang; Yu, Meng; Zhu, Yuyan; Yao, Yang (Frontiers in Genetics, 2021)
Background: Bladder cancer is a common malignant tumor characterized by high mortality and high management costs; however, it lacks useful molecular prognostic markers. Tribbles pseudokinase 3 (TRIB3) is a pseudokinase that participates in cell tumor progression and metabolism and whose function in bladder cancer is not precisely known. Main methods: We downloaded transcriptome data and clinical data of bladder cancer from associated databases and extracted the expression matrix of TRIB3 for multiple bioinformatics analysis. RT-PCR detected the expression of TRIB3 in bladder cancer cells. After knockdown of TRIB3 with siRNA, we investigated TRIB3 function using CCK8 and Transwell assays. Key findings: Kaplan–Meier analysis of TRIB3 in the four cohorts showed that high expression of TRIB3 correlated with poor outcome. Expression of TRIB3 positively correlated with stage and grade and down-regulation of TRIB3 expression significantly inhibited proliferation and migration of bladder cancer cells. Significance: TRIB3 is a potential prognostic marker and therapeutic target. It can be used to individualize the treatment of bladder cancer.